Quality of life and its relationship to motivation to live - an approach to the Saudi Arab model with the vision of 2030 - Samah, Belaid (International Journal of Psychosocial Rehabilitation, 2022)
the problem of this study attempts to present the quality of life and its relationship to motivation to life - a cognitive syndrome approaching the Saudi Arab model with the vision of 2030, by researching the following questions: What is the relationship between quality of life and motivation to live as a cognitive syndrome? And What is the plan of the Saudi Arabian project as a successful model in strengthening the relationship between quality in life and motivation to life? which has a good classification in the Arab and international standards of human and human development.